Tracking solar panel maximum power point using IoT-based mamdani fuzzy logic control - Nuryanti, Nuryanti; Erdani, Yuliadi; Subekti, Ruminto; Purnomo, Wahyudi; Indrajaya, Nathan; Badia, Bahdin Ahad (Jurnal Polimesin, 2025)
Renewable energy is an important solution to overcome the limitations of conventional non-renewable energy. The role and breakthroughs in using renewable energy are one of the research priorities that need to be developed and get more attention. Solar panels are one of the technologies in utilizing this energy source. However, with all the benefits of solar panels, the biggest challenge currently faced is the energy conversion system which still experiences fluctuations in output power due to unpredictable changes in solar irradiance, especially when covered by clouds. To overcome this problem, an effective Maximum Power Point Tracker (MPPT) system is needed. MPPT has feature limitations based on price, this is what drives the creation of an MPPT that is easy to develop. This study proposes the use of fuzzy logic methods in MPPT to determine the maximum point that needs to be achieved by solar panels. This study applies the INA226 sensor which is used to take data from solar panels, which is then processed into input to control MPPT by considering fuzzy conditions to maintain optimal power output. This research produces the final result in the form of a constant voltage required by the battery to fulfill the core function of SCC where the output is optimal through adjustment of the work cycle, so this research is expected to make data on solar panels easy to obtain and analyze with MPPT which can be developed in the future. The research can be considered as novel due to the implementation of fuzzy logic to determine control parameters